2013
DOI: 10.1177/1557988313493697
|View full text |Cite
|
Sign up to set email alerts
|

“Their Depression Is Something Different . . . It Would Have to Be”

Abstract: This study reports findings from the Black Women's Perceptions of Black Men's Depression (BWP) study, which included eight focus groups with Black women (N = 46) from southeastern Michigan. Four themes illustrated the impressions of Black women from different socioeconomic backgrounds: Black men's depression is a cultured and gendered phenomenon, the role of Black women in Black men's depression, intergenerational differences with how depression is handled by Black men, and the need (and ways) to reach Black m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Some evidence suggests that MDD and some other psychiatric disorders are qualitatively different for AA men than women [52,53]. In a study by Watkins and colleagues, AA women reported AA men’s depression to be qualitatively different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence suggests that MDD and some other psychiatric disorders are qualitatively different for AA men than women [52,53]. In a study by Watkins and colleagues, AA women reported AA men’s depression to be qualitatively different.…”
Section: Discussionmentioning
confidence: 99%
“…Such gender- and culture-specific approaches may be superior to strategies that ignore gender-specific culture of the target group. In addition, depressive symptoms and distress that may not necessarily meet the Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria require investigation [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Racial groups may differ in the effects of mental health problems, such as depression, on SEP indicators. Due to their worse access to the health care system, higher stigma, and a lower quality of treatment by the healthcare system [31], depression may be more disabling for African Americans than Whites [32]. In the NSAL data, Williams et al, showed that depression is more chronic for African Americans than Whites.…”
Section: Introductionmentioning
confidence: 99%
“…First, I will briefly highlight the advantages of using general-purpose word processing and spreadsheet software (i.e., Microsoft ® Word and Excel) as tools for organizing, reducing, and analyzing qualitative data for applied researchers (Meyer & Avery, 2009). Then I will present a quick and comprehensive method for analyzing qualitative data called the "rigorous and accelerated data reduction" (RADaR) technique that has been used in over a dozen qualitative and mixed methods projects (e.g., Jefferson, Watkins, & Mitchell, 2016;Kales et al, 2015;Watkins, Abelson, & Jefferson, 2013;Watkins, Allen, Goodwill, & Noel, 2016;Watkins & Gioia, 2015;Watkins, Wharton, Mitchell, Matusko, & Kales, 2015). Capitalizing on the depth and naturalistic relevance of qualitative analysis, the RADaR technique provides an expedited and user-friendly way of organizing, reducing, coding, and analyzing qualitative data to obtain findings from qualitative projects and disseminate these findings to relevant stakeholders.…”
Section: Introductionmentioning
confidence: 99%